The Study of Multiphase Flow for Petroleum Production Using Computational Fluid Dynamics (CFD) - Norhafizuddin, Husein @ Yusof (2013)
Petroleum is a highly valued natural resource where the used are never ending and the demand will always be higher than the supply. In order to keep up with the need of the world, there should be an enhanced way to recover the oil efficiently. Therefore, the flow of petroleum or gas through a vertical pipe from oil reservoir to platform/subsea system is significant to cater the enhancement of oil recovery. This research are based on this principle, and is more focused on the study for multiphase-flow pattern of petroleum production plus the turbulent coefficient effect on the bubbly flow in vertical pipe using Computational Fluid Dynamics (CFD) software. Multiphase-flow is chosen rather than the two-phase flow because the multiphase-flow are considered to be more realistic to give more accurate result thus easily implemented to a real situation. In studying the flow pattern of the multiphase-flow, the result obtains are manipulated with varying the velocity profile of each phase and observing which phase velocity gives a better flow of oil through the vertical pipe. While for the study of the turbulent coefficient effect on the bubbly flow in vertical pipe, firstly the simulation was run on the constant of bubbly flow to obtain the flow model. In this simulation, a turbulent coefficient of k-ε was introduced so the flow model was differed from the previous investigation and the velocity of particle inside the pipe was also observed. The research was developed in an enhanced model form using Gambit software and further simulated on Fluent simulation software. The results were then compared with previous work done by other researchers. The study is considered as success when all of the objectives are achieved with tremendous results. The result obtain shown that there are only 4 type of flow found during the petroleum production in a vertical pipe obtained. The investigation found that the turbulent flow do influence the particle flow whereas the particles fall down faster may due to gravitational pull acting on the flow. This also affects the composition at the end of the pipe.